Unveiling Indonesian EFL Textbooks Content: Lexical Density and Readability - Alifia Berlianti; Slamet Utomo; Atik Rokhayani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The complexity of reading text can be determined by lexical density and readability levels. The purposes of the research are to find the lexical density and readable level of reading text in local textbooks of Indonesian EFL. This research took a descriptive qualitative approach; the document of this study was fourteen reading text selected from each chapter from Modul Belajar Praktis Bahasa Inggris. The researcher grounded on Ure’s (1971) for lexical density and Flesch’s (1994) for determine readability level. After analyzing the data, the result show that all lexical density of the reading texts was high and the readability score ranging from 43.46 to 80.36. Based on Flesch’s (1994) from the fourteen reading texts from this textbook was classified into 5 level: easy for two texts, fairly easy for five texts, standard for two texts, fairly difficult for three and difficult for three.